Cultural diplomacy and the reconfiguration of global geostrategic narratives: African positionality in a multipolar order - Munyangeyo, Theophile (My University, 2026)
Abstract As global power configurations shift toward an increasingly multipolar order, cultural diplomacy has emerged as a critical instrument in the reconfiguration of influence and partnership within the Global Majority. This paper examines how multipolarity is reshaping cultural hegemony, with a particular focus on Africa as a central arena of geopolitical, cultural, and epistemic contestation. Moving beyond materialist accounts of power, the study investigates how emerging and non-Western actors engage African states and societies through culturally resonant, affective, and identity-based forms of diplomacy that challenge long-standing Eurocentric dominance. Using a qualitative research design grounded in critical discourse analysis and policy review, the paper draws on interdisciplinary frameworks from postcolonial theory, decoloniality, international cultural relations, associationism, and soft power studies. Through comparative case studies of China-Africa, Qatar-Africa, Russia-Africa, and Turkey-Africa relations, the research illustrates how cultural diplomacy emphasising mutual respect, historical solidarity, sovereignty, and shared values is increasingly displacing Western models rooted in conditionality and normative hierarchy. The findings reveal that emerging powers are more effective in fostering durable partnerships when cultural diplomacy prioritises emotional intelligence, recognition, and narrative alignment rather than transactional service delivery or ideological persuasion. These dynamics signal a broader shift in cultural hegemony within a multipolar global system, in which Africa exercises greater agency in navigating competing influences. The paper contributes to debates on decolonisation and global governance by demonstrating that cultural diplomacy is central, rather than peripheral, to contemporary geopolitical transformations and calls for African-led cultural strategies that leverage multipolarity to advance sovereign, balanced, and culturally grounded international relations and partnerships. Keywords: cultural diplomacy, cultural hegemony, decoloniality, geostrategy, global majority, multipolarity.
PUBLISHED
Keywords: cultural diplomacy; cultural hegemony; decoloniality; geostrategy; global majority; multipolarity; Inclusive Society; International Development; International Integration